Fossil Versus Nonfossil CO Sources in the US: New Airborne Constraints From ACT‐America and GEM. Issue 11 (5th June 2021) - Gonzalez, Andres; Millet, Dylan B.; Yu, Xueying; Wells, Kelley C.; Griffis, Timothy J.; Baier, Bianca C.; Campbell, Patrick C.; Choi, Yonghoon; DiGangi, Joshua P.; Gvakharia, Alexander; Halliday, Hannah S.; Kort, Eric A.; et al.
Abstract: Carbon monoxide (CO) is an ozone precursor, oxidant sink, and widely used pollution tracer. The importance of anthropogenic versus other CO sources in the US is uncertain. Here, we interpret extensive airborne measurements with an atmospheric model to constrain US fossil and nonfossil CO sources. Measurements reveal a low bias in the simulated CO background and a 30% overestimate of US fossil CO emissions in the 2016 National Emissions Inventory. After optimization we apply the model for source partitioning. During summer, regional fossil sources account for just 9%–16% of the sampled boundary layer CO, and 32%–38% of the North American enhancement—complicating use of CO as a fossil fuel tracer. The remainder predominantly reflects biogenic hydrocarbon oxidation plus fires. Fossil sources account for less domain‐wide spatial variability at this time than nonfossil and background contributions. The regional fossil contribution rises in other seasons, and drives ambient variability downwind of urban areas. Plain Language Summary: Carbon monoxide (CO) is an air pollutant emitted from fossil fuel combustion and from forest and agricultural fires. CO is also produced in the atmosphere through the oxidation of hydrocarbons from both natural and human‐caused sources. US fossil fuel CO emissions have been declining in recent years, and their current importance relative to other regional sources is uncertain. Here, we interpreted a large group of aircraft‐based CO measurements with a high‐resolution atmospheric model to better quantify US fossil and nonfossil fuel CO sources over the eastern half of the US. We find that US fossil fuel CO emissions in the 2016 National Emissions Inventory are overestimated by ∼30%. Furthermore, during summer regional fossil fuel sources account for only a small fraction of the CO over North America compared to the background concentrations already present in air entering North America, and compared to the regional source from natural hydrocarbon oxidation. This complicates the use of CO as a tracer for estimating fossil fuel sources of other pollutants such as carbon dioxide. Key Points: We interpret an ensemble of airborne measurements with the GEOS‐Chem model to constrain US fossil fuel and nonfossil carbon monoxide (CO) sources Measurements reveal an approximate 30% overestimate of US fossil fuel CO emissions in the National Emissions Inventory During summer regional fossil fuel sources account for just 9%–16% of total boundary layer CO over eastern North America